2004
DOI: 10.1258/002221504323012030
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life and functional evaluation after supracricoid partial laryngectomy with cricohyoidoepiglottopexy in Mexican patients

Abstract: This study assessed the functional results in patients treated primarily through supracricoid partial laryngectomy (SCPL) with cricohyoidoepiglottopexy (CHEP). Fifteen patients with a diagnosis of epidermoid carcinoma of the glottis region admitted to the Instituto Nacional de Cancerología (México) between June 2001 and September 2002 were studied. Three patients were at stage I, five at stage II, six at stage III, and one at stage IV. Both cricoarytenoid units were preserved in 12 patients, and only one in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
3
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 9 publications
2
13
3
1
Order By: Relevance
“…To our knowledge, this is the first report of a detailed functional evaluation in an aged population after SCL. The functional results after SCL have been reported by different authors around the world 1–9, 23–29. In all the series, patients aged over 65 years, frequently up to the late 70s, have been included, suggesting that SCL are routinely performed also on old patients.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…To our knowledge, this is the first report of a detailed functional evaluation in an aged population after SCL. The functional results after SCL have been reported by different authors around the world 1–9, 23–29. In all the series, patients aged over 65 years, frequently up to the late 70s, have been included, suggesting that SCL are routinely performed also on old patients.…”
Section: Discussionmentioning
confidence: 95%
“…Several investigators have demonstrated the SCL to be an oncologically sound alternative to total laryngectomy (TL), the standard technique for advanced‐stage laryngeal carcinoma, with similar local control and survival rates 2, 3. Since being first developed and adopted in Europe, SCLs have gained an increasing acceptance in North America and around the world 4–6. The advantage of SCL over TL is that a permanent tracheostoma is not required, since the main laryngeal functions (respiration, phonation, and swallowing) are preserved, when at least one functioning cricoarytenoid joint is maintained, facilitating neoglottal competency.…”
Section: Introductionmentioning
confidence: 99%
“…46 Partial laryngectomy appeared in one report to have the lowest psychosocial impact of the most commonly used modalities, 47 and SCPL was even found to result in almost normal biopsychosocial integration in a given patient population. 48 Certain factors were found to limit the potential for QOL preservation after partial laryngectomy: SCPL with cricohyoidoepiglottopexy generally produces excellent QOL, but the rare scenario of inability to decannulate or comorbid association of radiotherapy or cervical lymphadenectomy seem to affect QOL scores negatively. 49 Nonetheless, salvage partial laryngectomy was noted to have acceptable functional-and oncologic-outcomes in carefully selected patients with stage I or II laryngeal disease not responding to definitive radiotherapy, making it a useful alternative to TL.…”
Section: Quality Of Life After Conservation Surgerymentioning
confidence: 99%
“…Good contact between the epiglottis and arytenoid with contact vibrations are the prerequisite for satisfactory voice function. The presence of one or both arytenoids does not affect the voice quality significantly 13 , but, on the other hand, preservation of both arytenoid shortens the time of swallowing rehabilitation 14 . After SCHLP, all types of laryngeal movements during phonation were recorded.…”
Section: Discussionmentioning
confidence: 98%